Denotative and Connotative Meanings in the Dialogue of Capernaum: A Semiotic Approach to Nadine Labakiâ€™s Work - Meisyaroh, Fitria; Dayudin, Dayudin; Rohanda, Rohanda (Alibbaa’: Jurnal Pendidikan Bahasa Arab, 2025)
The study of denotative and connotative meanings in the Arabic language remains limited, particularly regarding how meanings evolve within social and ideological contexts in films. Most previous research has predominantly focused on semantic analysis without considering the connotative aspects that shape social perceptions and representations. This study aims to analyze the denotative and connotative meanings of selected Arabic words using a qualitative approach through the perspective of Roland Barthes’ Semiotics. Data were collected through non-participant observation and note-taking, while analysis was conducted using extralingual referential analysis, employing both comparative and contrastive methods. The findings reveal that words such as Ù‚ÙŠÙˆØ¯, Ø§Ù„Ø¬ØÙŠÙ…, Ø§Ù„Ø¥ÙŠØ¬Ø§Ø±, Ø®Ø§Ø¯Ù…Ø©, and Ø§Ù„Ù‡Ø§Ø±Ø¨ in the film Capernaum carry connotative meanings that reflect social constraints, suffering, exploitation, oppression, and the loss of identity. This study affirms that language is not merely a tool for communication but also an ideological instrument that represents social realities. This study implies that connotative meaning can enrich linguistic studies and provide deeper insights into language use across various social and cultural contexts.